The Importance of the Speed Execution in the Technical Procedures Specific to the Style Ashihara Karate - D. Mocioaca; M. Dragomir (Editura Universitatii Transilvania din Brasov, 2023)
This article brings to the attention of specialists in the field, considerations regarding the determining character of the execution speed in the technical procedures that are specific to the training of Ashihara Karate practitioners. The purpose of the research is to determine the influence that the development of execution speed has on technical training, and implicitly on sports performance. The experimental research took place over 8 weeks, including 15 athletes, and members of the Sen Craiova Sports Club, aged between 20 and 35. Following the analysis of the results, we emphasize the importance of improving the execution speed of specific training techniques in obtaining an optimal competitive performance.